Assessing lower extremity loading during activities of daily living using continuous-scale physical functional performance 10 and wireless sensor insoles: a comparative study between younger and older adults. - Häckel, Sonja; Kämpf, Tobias; Baur, Heiner; von Aesch, Arlene; Kressig, Reto Werner; Stuck, Andreas Ernst; Bastian, Johannes Dominik (European Journal of Trauma & Emergency Surgery, 2023)
Purpose: This study aims to investigate the lower extremity loading during activities of daily living (ADLs) using the Continuous Scale of Physical Functional Performance (CS-PFP 10) test and wireless sensor insoles in healthy volunteers. Methods: In this study, 42 participants were recruited, consisting of 21 healthy older adults (mean age 69.6 ± 4.6 years) and 21 younger healthy adults (mean age 23.6 ± 1.8 years). The performance of the subjects during ADLs was assessed using the CS-PFP 10 test, which comprised 10 tasks. The lower extremity loading was measured using wireless sensor insoles (OpenGo, Moticon, Munich, Germany) during the CS-PFP 10 test, which enabled the measurement of ground reaction forces, including the mean and maximum total forces during the stance phase, expressed in units of body weight (BW). Results: The total CS-PFP 10 score was significantly lower in older participants compared to the younger group (mean total score of 57.1 ± 9.0 compared to 78.2 ± 5.4, respectively). No significant differences in the mean total forces were found between older and young participants. The highest maximum total forces were observed during the tasks 'endurance walk' (young: 1.97 ± 0.34 BW, old: 1.70 ± 0.43 BW) and 'climbing stairs' (young: 1.65 ± 0.36 BW, old: 1.52 ± 0.28 BW). Only in the endurance walk, older participants showed a significantly higher maximum total force (p < 0.001). Conclusion: The use of wireless sensor insoles in a laboratory setting can effectively measure the load on the lower extremities during ADLs. These findings could offer valuable insights for developing tailored recommendations for patients with partial weight-bearing restrictions.